1997
DOI: 10.1023/a:1008287922285
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survivors of small-cell lung cancer (SCLC): A French multicenter study

Abstract: Physical, mental and psychological states were considered as normal at 30 months in respectively 70.3%, 87.7% and 67.7% of patients, not influenced by prophylactic cranial irradiation, number of chemotherapy cycles, CCNU or cisplatin. Therapeutic sequelae were neurological impairment (13%), pulmonary fibrosis (18%) and cardiac disorders (11%) at 30 months. Return to work was possible for 40% of patients in the first two years following diagnosis. Among 43 relapsing patients, 33 benefited from a second-line tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The study also identified the following three prognostic subgroups for patients receiving cisplatin chemotherapy that had significantly distinct survival expectations: based on performance status, age, and hemoglobin and serum LDH levels. Other studies employing secondary analysis of clinical trial information have reached similar con- 54 Performance status 12,15,53,55-60 SVCO 1 Additional factors Anatomic Sex 12,52,56 "T" factor 10 Symptoms 27,60 "N" factor 10 Age 12 Clinical stage IIIA vs IIIB 61 Number of sites involved 12,53,62 Pleural effusion 63 Liver metastases 64 Clinical chemistry/hematology Hemoglobin 12,15,38,60 LDH 12 Albumin 57 New or promising factors Clinical chemistry/hematology Quality of life [16][17][18] Coagulation factors [65][66][67][68] Marital status 16 Proteinuria 69 Depressed mood 70 CYPIA1 37 Proliferation markers DNA ploidy and/or % S-phase 71 Ki-67 72 Other molecular biologic markers Replication errors 2p/3p 73 clusions, 13 as have retrospective studies of patients who were not enrolled in clinical trial protocols. 14,15 New and promising prognostic factors also are listed in Table 2.…”
Section: Advanced Diseasementioning
confidence: 96%
“…The study also identified the following three prognostic subgroups for patients receiving cisplatin chemotherapy that had significantly distinct survival expectations: based on performance status, age, and hemoglobin and serum LDH levels. Other studies employing secondary analysis of clinical trial information have reached similar con- 54 Performance status 12,15,53,55-60 SVCO 1 Additional factors Anatomic Sex 12,52,56 "T" factor 10 Symptoms 27,60 "N" factor 10 Age 12 Clinical stage IIIA vs IIIB 61 Number of sites involved 12,53,62 Pleural effusion 63 Liver metastases 64 Clinical chemistry/hematology Hemoglobin 12,15,38,60 LDH 12 Albumin 57 New or promising factors Clinical chemistry/hematology Quality of life [16][17][18] Coagulation factors [65][66][67][68] Marital status 16 Proteinuria 69 Depressed mood 70 CYPIA1 37 Proliferation markers DNA ploidy and/or % S-phase 71 Ki-67 72 Other molecular biologic markers Replication errors 2p/3p 73 clusions, 13 as have retrospective studies of patients who were not enrolled in clinical trial protocols. 14,15 New and promising prognostic factors also are listed in Table 2.…”
Section: Advanced Diseasementioning
confidence: 96%
“…Aging of the general population and advancements in early detection and treatment79, 80 will further increase the LTLC survivors in the population. Sometimes in the past, over a 30-month survival after a SCLC diagnosis was regarded as LTLC survivors 81. The majority of these LTLC survivors have undergone invasive treatment such as lung resection, radiation therapy, and/or chemotherapy; comorbidity burden in these survivors is especially high when compared to survivors of other cancer sites 82.…”
Section: Quality Of Life: Psychosocial-behavioral Characteristics mentioning
confidence: 99%
“…The cessation of cigarette smoking after successful therapy is associated with a significantly decreased risk of an SPM [7]. The risk of SPM was increased by a number of chemotherapy cycles > 6, an age of > 60, treatment with combination chemotherapy, and chest irradiation [8,9]. In a study including sixty-one patients who survived for more than two years, SPM was observed in seven patients (four with non-small cell lung cancer, two with gastric cancer, and one with prostate cancer) [10].…”
Section: Discussionmentioning
confidence: 99%